2017
DOI: 10.3892/ijo.2017.4074
|View full text |Cite
|
Sign up to set email alerts
|

AEG-1 associates with metastasis in papillary thyroid cancer through upregulation of MMP2/9

Abstract: Astrocyte elevated gene-1 (AEG-1), known as an oncogene, is overexpressed in various cancers and implicated in tumor progression and metastasis. However, its functional significance and underlying molecular mechanisms in thyroid cancer remain to be elucidated. In the present study, we detected the potential function of AEG-1 in papillary thyroid cancer (PTC). We also investigated the relation between AEG-1 and matrix metalloproteases (MMP)2 and 9 through immunohistochemistry, western blotting, real-time PCR, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 31 publications
(35 reference statements)
1
43
0
Order By: Relevance
“…36 Studies have shown that the expression of MMP-2 and MMP-9 is positively correlated with lymph node metastases and degree of tumor invasion in PTC. 37,38 In order to further verify the correlation of UCA1 expression with cervical lymph node metastasis, IHC experiments were carried out to verify the correlation between UCA1 and lymph node metastases. We detected high levels of MMP-2 and MMP-9 in samples with high UCA1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…36 Studies have shown that the expression of MMP-2 and MMP-9 is positively correlated with lymph node metastases and degree of tumor invasion in PTC. 37,38 In order to further verify the correlation of UCA1 expression with cervical lymph node metastasis, IHC experiments were carried out to verify the correlation between UCA1 and lymph node metastases. We detected high levels of MMP-2 and MMP-9 in samples with high UCA1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has two outstanding features. The first is the high rate of metastasis to lymph nodes or other organs, which is as high as 30% to 59.1% . The second is the resistance to chemotherapy and conventional external beam radiotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer is one of the fastest growing cancers worldwide. 1,2 It has two outstanding features. The first is the high rate of metastasis to lymph nodes or other organs, which is as high as 30% to 59.1%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also found that PTC is associated with overexpression of MMP-1, MMP-2, MMP-7, MMP-9, and MMP-13. [11][12][13][14][15][16][17] However, few studies have reported on the correlation between PTC and other MMPs or the regulatory mechanisms of MMP expression in PTC. In the current study, we found that MMP-11 played an important role in the development of PTC.…”
Section: Introductionmentioning
confidence: 99%